BIMBINGAN DAN PENGENALAN DAKWAH PADA KELOMPOK USIA SEKOLAH TAMAN KANAK-KANAK - Sefrita Nurkhabibah (Jurnal Bimbingan Penyuluhan Islam, 2022)
The main problem of this research is the learning management of Kindergarten students. This article is built with the following sub-problems, How is the da'wah program at school age Kindergarten about How to implement Kindergarten School Age group learning, Types of researchThis is a qualitative research with a management theory approach.The data sources for this research are primary data sources with five informants (principals, teachers and parents) and secondary data sources.The data collection methods used are observation, interviews and documents.Analytical processing techniquesthe data is data reduction, data presentation, and drawing conclusions.The results of this study indicate that planning Guidance and Introducing Da'wah in the Kindergarten School Age Group must be optimally managed, new innovations in the work program do not only focus on the study of the Koran.And the introduction of Da'wah in Kindergarten School Age Groups must be carried out and socialized to the fullest.Give motivation, give advice, if there is free time.